Artificial Intelligence as a Catalyst for Social Entrepreneurship and Volunteering Engagement - Toncheva-Zlatkova, Violeta (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Social entrepreneurship often emerges from grassroots volunteering driven by solidarity and local knowledge. Against the backdrop of rapid technological change, artificial intelligence (AI) acts as a catalyst, converting voluntary engagement into scalable social innovations. This paper explores how AI facilitates the transition from informal volunteering to structured social entrepreneurship models that stimulate economic development and job creation. Drawing on social innovation theory and the RBV, the study analyzes how AI tools - such as skill-matching algorithms, predictive models for community needs, and digital impact measurement platforms - enhance organizational capacity and social inclusion. The paper further examines governance and ethical implications, arguing that AI-driven social entrepreneurship can support ESG transformation when technological innovation remains aligned with solidarity and human-centered development. By integrating AI, grassroots initiatives transcend traditional boundaries, creating sustainable value and fostering inclusive growth in the digital era.